Dampak Peran Media Sosial dalam Penyebaran Aliran Sempalan di Kelurahan Tegal Sari Mandala I - Shabrina Shabrina; Indra Harahap (STIKes Ibnu Sina Ajibarang, 2024)
Increasingly sophisticated technology provides major changes in communication carried out by every society in the modern era. Entering the era of globalization, teenagers are among those who often use internet media, especially social media, as a means of searching for information. With social media, we can see the latest information about what situations are happening. A splinter sect is a sect that is often seen as a protest against self-division from the majority, exclusive attitudes, firm but rigid stances, monopoly on truth, and fanaticism